The biomechanical effects of Ti versus PEEK used in the PLIF surgery on lumbar spine: a finite element analysis. Issue 10 (7th September 2021) - Wang, Hongwei; Wan, Yi; Liu, Xinyu; Ren, Bing; Xia, Yan; Liu, Zhanqiang
Abstract: Titanium (Ti) and polyetheretherketone (PEEK) are commonly used in posterior lumbar interbody fusion (PLIF). The study investigated biomechanical effects of Ti versus PEEK used as materials of cage and rods on the lumbar spine. Four different configurations of PLIF were constituted. Stiff Ti rods provided satisfactory initial stability but increased the stress on rods significantly under simulated physiological load conditions. Ti cage increased the stress on bone endplates significantly. Materials of cage and rods had insignificant effects on the nucleus pressure and facet joint force of non-instrumented segments. Further clinical studies and follow-up observations are essential for corroborating these findings.